A study into growth and anaemia in children with epidermolysis bullosa. (1st June 2020) - Reimer, A.; Hess, M.; Schwieger‐Brie, A.; Kiritsi, D.; Schauer, F.; Schumann, H.; Bruckner‐Tuderman, L.; Has, C.
Summary: Severe subtypes of epidermolysis bullosa (EB) are devastating conditions that cause extremely fragile skin and mucosal membranes and lots of wounds. So far, no cure for EB exists. About 5, 000 people in the U.K. and 500, 000 people worldwide suffer from different EB types. Apart from skin problems, children with EB often have trouble gaining weight, and they develop anaemia (deficiency of iron). As wound healing works best when the body is strong, researchers needed to see how exactly children with EB grow and what factors may stop them from growing properly. To address this, a research group from the German EB reference centre, has looked back at weight, height and blood measurements of 200 children with EB. 157 had a type of EB called recessive dystrophic EB (RDEB) and 43 had junctional EB (JEB). The researchers calculated growth charts that allowed better comparison with growth of healthy children and can help to find EB‐specific growth patterns. The researchers found that the growth of children with RDEB was impaired from the second year of life (age 18 months+). In JEB, growth resembled that of healthy children. Anaemia was present from the second year of life onwards in RDEB and JEB. Children with RDEB who suffered from anaemia and deficiency of proteins, vitamins and certain minerals in the blood had impaired growth compared to those who did not. A lot of inflammation in the body also compromised the growth of children with EB. The EB growth charts from this study will help doctors and families in making decisions on feeding, like giving extra vitamins or tube feeding. The results are also important now that therapies for EB are being developed, so that we can compare how growth will improve in line with such therapies. The direct results of this study are printable growth charts that can be used throughout the world immediately, to assess and counsel children with EB. This is a summary of the study: Natural history of growth and anaemia in children with epidermolysis bullosa: a retrospective cohort study